The effect of external factors on project perfomance of water and wastewater construction companies in Oman with moderating effect of organizational structure - Mohamed Alghammari, Mohamed Nasser (2024)
The progress of any country is closely tied to the growth of its construction industry. The development of a construction project requires varying levels of work and a lot of input from both the governmental and private sectors. Construction project performance is critical for the country’s economic development, and there are a variety of elements that influence it. The objective of this study is to examine the effect of project external factors and organizational structure on the project performance of construction companies in the water and wastewater sector in Oman. The most important project external factors were selected in this study to explore the effect of these external factors on project performance with the organizational structure. The population for this study was the construction companies operating in the water and wastewater sector in Oman. This quantitative study was carried out with a survey questionnaire. A total of 113 questionnaires were received from project managers of construction companies. Data were analyzed using Statistical Package for Social Sciences software for descriptive, reliability, validity, and regression analyses. This study was successful in achieving its goals by looking at a variety of external factors and examining the organizational structure that has a substantial effect on the performance of construction projects. The findings of the study provide a comprehensive understanding of the various project parameters required to improve project performance, especially in Oman’s water and wastewater sector. This is consistent with the industry’s observation that technical improvements are causing quick shift in the conventional project management paradigms. In addition to the above, this study demonstrated that organizational structure has a significant effect on project success in Oman’s construction firms in the water and wastewater sector. In summary, contractor, customer, and project management elements are the most crucial project-related aspects for medium- and largesized construction enterprises.